Pengobatan penyakit tumor mammae melalaui operasi (matektomi dan ovariohisterektomi) dan kombinasinya (tanaman herbal) pada hewan - Gunanati Soedjono; Bambang Pontjo Priosoeryanto; Ietje Wientarsih; Ros Sumarny (Institut Pertanian Bogor, 2009)
Tumor or neuplasm can be meant as a abnormal and uncontrol growth of the transformation tissue or the change of one or main location of the body. This degenerative desease is one of the deseases in the animal pet especially dog and cat. Generaly this tumor deseases can be used with therapy using surgery and usually will relapse after six months. from our previous research had succeded to examp by using activity in vitro antiproliverati from extract plant (nusa indah, blustru and temu putih) combined with recombinanct interferon dog ( rCaiFN). The above phenomenon indicate a new hope to make a therapy for tumor desease, especially for dog and cat and may be in the future can be used for human. In this research we used 21 female rabbits and divided into 7 treatment groups, consisted of 3 rabits ie : group A. negative control; B. surgery, preventive and curative curcumine; C. positive control; D. positive control and surgery; E. surgery and preventive zedoaria capsul; F. surgery , preventive and curative zedoaria capsule and G. surgery and curative zedoaria capsule . Induction with carcinogen (MNU) treated every weeks during 3 weeks. Surgery is executed in the 5 weeks and giving capsule zedoaria is executed every day for 4 weeks (preventive or curative) and 8 weeks (preventive andcurative). Result of the research indicated that mammae tumor has been made successfully by MNU (n-metil-nnitrosuria) induction to rabit and capsule zedoaria and it has been treated by doing surgery therapy (mastectomy and ovariohisterectomy). Also decombination of zedoaria capsule. The result of the research indicated lindrance of tumorgenesis to the group which is given by zedoaria capsule. from the clinical picture shows that zedoaria capsule does not give negative effect to clinical picture (temperature, respiratory frequency and heart rate)/ still normal to all the groups. Tumor induction with (MNO) at mammary gland will occur allegic reaction inflammatory which is the beginning of tumor mechanism which is marked by total leucosit, neutrofil, eosinofil, and basofil increase. Tumor therapy with surgery (masektomi and ovariohisterektomi) and the combination with rimpang Temu Putih capsule can decrease the number of leucosit, neutrofil and limfosit but only a little affectmonosit number, although statistically it does not show real difference.